Tvs legislativas e sua relação com a interatividade, produção de conteúdo, design audiovisual e audiência - Santos, Rodolpho Raphael de Oliveira (2019)
With the reconfiguration of the technology and the transition from an era to an era where converging the connection is done, it has been constant in individualization of content the center point of a powerful debate about audience and content production reflecting the interactivity in TVs in Brazil, especially the Legislative TVs where the focus of the research will be directed to the experiences of the contexts: national (TV camera and TV Senate) and local (TV House PB and TV Camera João Pessoa). The main objective of this research is to explore the relationship of these TVs from the interactivity and at the same time, check that the form occur the movement and spread of content and what your relationship with the audience. Taking into consideration that this for your time, can contribute to the construction of a more participative and dynamic model from the media streams, as well as, the major events are responsible for large-scale growth of the audience of these stations which in your time, going on to become fragmented as a result of the participation of the individual in the most diverse platforms reflection of the phenomenon of propagabilidade and audiovisual enjoyment. The methodology was based on the analysis of content that uses systematic procedures and objectives description of contents of messages. Having knowledge inference concerning production conditions (or eventually, reception) and associated with it the application of audiovisual design (DA) highlighting the roles of synthesizer, modifier and producer as well as the motivation for participation in this process. The results explain the low ratings of these TVs which focuses on content production and with the possibility of uplift to the broadband system to spread open and content on demand